Rank estimators versus least square estimators for estimating the parameters of semiparametric accelerated failure time model - Karimi, Mostafa; Ibrahim, Noor Akma (Juniper Publishers, 2019)
Rank-based method and least square approach are the most common techniques for estimating the regression parameters of accelerated failure time model. In this study, both inference procedures are considered their advantages and disadvantages are explained and their similarities and differences are discussed.